Timely N-Acetyl-Cysteine and Environmental Enrichment Rescue Oxidative Stress-Induced Parvalbumin Interneuron Impairments via MMP9/RAGE Pathway: A Translational Approach for Early Intervention in Psychosis. (3rd June 2021) - Dwir, Daniella; Cabungcal, Jan-Harry; Xin, Lijing; Giangreco, Basilio; Parietti, Enea; Cleusix, Martine; Jenni, Raoul; Klauser, Paul; Conus, Philippe; Cuénod, Michel; Steullet, Pascal; Do, Kim Q
Abstract: Research in schizophrenia (SZ) emphasizes the need for new therapeutic approaches based on antioxidant/anti-inflammatory compounds and psycho-social therapy. A hallmark of SZ is a dysfunction of parvalbumin-expressing fast-spiking interneurons (PVI), which are essential for neuronal synchrony during sensory/cognitive processing. Oxidative stress and inflammation during early brain development, as observed in SZ, affect PVI maturation. We compared the efficacy of N-acetyl-cysteine (NAC) and/or environmental enrichment (EE) provided during juvenile and/or adolescent periods in rescuing PVI impairments induced by an additional oxidative insult during childhood in a transgenic mouse model with gluthation deficit ( Gclm KO), relevant for SZ. We tested whether this rescue was promoted by the inhibition of MMP9/RAGE mechanism, both in the mouse model and in early psychosis (EP) patients, enrolled in a double-blind, randomized, placebo-controlled clinical trial of NAC supplementation for 6 months. We show that a sequential combination of NAC+EE applied after an early-life oxidative insult recovers integrity and function of PVI network in adult Gclm KO, via the inhibition of MMP9/RAGE. Six-month NAC treatment in EP patients reduces plasma sRAGE in association with increased prefrontal GABA, improvement of cognition and clinical symptoms, suggesting similar neuroprotective mechanisms. The sequential combination of NAC+EE reverses long-lasting effects of an early oxidative insult on PVI/perineuronal net (PNN) through the inhibition of MMP9/RAGE mechanism. In analogy, patients vulnerable to early-life insults could benefit from a combined pharmacological and psycho-social therapy.